Development of Learning Multimedia on Formal Object Material and Geography Material Objects for Class X SMA - Aldonia, Jihan; Kurnia Yusri, Meldi Ade; Bentri, Alwen; Rayendra, Rayendra (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to develop instructional multimedia designed using Microsoft Office PowerPoint for the topics of formal and material objects in geography for 10th-grade students in Senior High School (SMA). The research follows the Borg and Gall model through stages of planning, initial product development, validation, testing, and final product. Instructional multimedia is created by utilizing Microsoft Office PowerPoint technology as a tool to create relevant presentation slides aligned with the Geography curriculum.The results of this study demonstrate that the developed instructional multimedia effectively enhances students' understanding of the concepts of formal and material objects in geography. Furthermore, this multimedia is considered a highly efficient tool in boosting motivation and interest in learning geography among students. Student satisfaction surveys and teacher interviews indicate that the instructional multimedia received positive responses from all parties.This research provides a significant contribution to the development of innovative and technology-relevant instructional media. It is hoped that the use of this multimedia will improve students' comprehension of formal and material object topics in geography and offer a more engaging and effective learning alternative in Senior High School.